Army veterans means in spending the financial incentive SVTB1Malaysia/ Mohd Zahid Laton and Harlina Yunus @Junor - Laton, Mohd Zahid; Yunus @Junor, Harlina (2013)
In the Malaysian Budget 20I3 announcement, the Prime Minister has proposed compensation in the form of financial aid to the army veterans who did not opt for the pension scheme after retiring from the military services. The amount of compensation is RMI,000. 00 and will start disburse in January 20I3. This is a one off payment and army veterans should spend their money wisely. This survey will study the purpose of money spent by the army veterans and the type of expenditure whether for individual, family, and other purposes. The population of this study is the army veterans who live in the area of Wilayah Jengka, Kota Gelanggi, and Kuala Krau. The study was conducted during the distribution of the form SVTB1Malaysia.